The Effectiveness of Think Talk Writing and Guided Writing Techniques on Teaching Descriptive Writing for the Tenth-Grade Students of SMK Swasta Yayasan Abdi Karya Torganda - Pasaribu, Dian Polotangi Pandapotan; Manik, Sondang; Sinambela, Erika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research presents a research report on the using of Think Talk Writing (TTW)Method and Guided Writing Techniques for students’ writing skill at SMK Swasta Yayasan Abdi Karya (Yadika) Torganda . The objectives are to find out the effect of using Think Talk Writing (TTW) and Guided Writing Techniques (GWT) for students’ writing skill and which method is the most effective one. It was by using classroom action research. The subject of this study were grade X students of Convesional High School at SMK Swasta Yayasan Abdi Karya (Yadika) Torganda. In this study the writer took 105 students of SMK Swasta Yayasan Abdi Karya (Yadika) Torganda a as the sample. They were divided into three groups. The first and the second groups are (Experimental Group). They were taught by using Think Talk Writing (TTW) and Guided Writing Techniques (GWT) in writing text, while the third group (Control Group) was taught without using Think Talk Writing (TTW) and Guided Writing Techniques (GWT). The technique for data analysis is quantitative research. In analyzing the data the mean of the students score for pre-test in experimental group one (TTW ) is 69,27 and the mean of the students score for post-test in experimental group one is 81,30. The mean of the students score for pre-test in experimental group two (GWT)  is 68,83 and  the mean of the students score for post-test in experimental group two is 80,29.The mean for pre-test in control group is 66,8 and the mean for post-test in control group is 76,77 The conclusion is that the using of Think Talk Writing (TTW) and Guided Writing Techniques (GWT)  are significantly affect the students’ writing skill.TTW is the most effective one in teaching News Item Text than GWT . It is suggested that teachers should apply this method as one of methods to improve students’ Ability in Writing Descriptive Text.